Models for Interactions in Boundary Layers at Rotational Motions in Noncircular Orbits: The Concept for Teaching Science - Lena J-T Strömberg (Universitas Pendidikan Indonesia (UPI), 2022)
The motions of a boomerang, a tennis ball with spin, and a flock of birds are studied with the assumption that, occasionally, capture into a noncircular orbit (NCO) is ruling the behavior. This approximation will be used in applications when the orbit is almost circular, but the angular velocity varies due to the interaction between orbital and sidereal motion. A format with decreasing radius is exploited, to model drop, due to spin. Collection and exchange by generalized conjugated forces from energy are extracted with a semi-derivative, which appears to give no loss, but only contributions. It is proposed that the collection of energy in surrounding air layers of a certain shape may be beneficial for propulsion. Since the analyses were based on daily life conditions, this can be applied for a support media in teaching science.